Theoretical Approach to Study the Nature and Structure of Organotin (IV) Derivatives - Abdul-Hameed, Fatma M (Al-Nahrain Journal of Science, 2018)
A theoretical study of semi-empirical calculation of PM3 level was used to characterize three Tin complexes (R2SnL2) [where (R): (Phenyl), (butyl) and (methyl) and L: (N-tolyl -m-methoxybenzo hydroxamic acid) ]. The comparison of the three complexes that have different (R) had been done on the basis of calculated energies and physical properties of the molecular model systems, such as heat of formation, HOMO-LUMO gap, binding energy, dipole moment, surface area. This present study revealed a clear picture and useful information about the nature of complex stability of the three Tin complexes R2SnL2